Regulatory framework for Member-owned Islamic Microfinance Institutions (MIMIS) In Sub-Saharan Africa (SSA) - Owolabi Yusuf, Muhammad-Bashir; Shirazi, Nasim Shah; Abdullah, Moha Asri (Islami Bank Training and Research Academy (IBTRA), 2016)
Member-owned Islamic microfinance institutions have been toasted to be the alternative means of financial inclusion among the Muslims who are voluntarily excluded from participating in the traditional member-owned microfinance institutions because of the interest they charge. This novel idea is still new and little is known about its operations and regulations guiding its operations. This paper surveys the practices of the common member-owned Islamic microfinance in Sub-Saharan Africa with a view of recommending a regulatory framework for its operations based on these practices. This paper, thus, proposes a number of regulations for the operation of both Islamic Saving Groups and Financial Cooperative. It is hoped that these proposed regulations will assist the operators, policy makers and donor agencies to chat a way of improving the financial inclusiveness of the poor who are excluded from benefiting from the available member-owned microfinance institutions with a view to lift them out of poverty.